PENERAPAN STANDARD OPERATIONAL PROCEDURE OLEH BELL SERVICE AGENT DALAM MENANGANI BARANG BAWAAN TAMU INDIVIDUAL CHECK-IN DI HOTEL INDIGO BALI - Widhiastuty, Ni Luh Putu Sri; Trianingrum, Ni Nyoman Nidya; Pratama, I Made Adi (Universitas Triatma Mulya, 2022)
ABSTRACT The purpose of this research is to find out how the implementation of the Standard Operational procedure for handling the luggage of individual guest check-in and the obstacles faced by the Bell Service Agent in implementing the Standard Operational procedure for handling the luggage of individual guests check-in, so that efforts can be identified. done by the Bell Service Agent in dealing with these problems. This research uses interview, observation and documentation methods with descriptive qualitative data techniques. In this study what must be known is the Standard Operational Procedure for handling the luggage of individual guests checking in by presenting the results of interviews, observations and documentation. It can be concluded that the Standard Operational Procedure for handling guest luggage is carried out by Bell Service Agents with constraints such as several Bell Service Agents. have not applied guest luggage handling techniques, goods storage places are always full, lack of communication during handling of goods, and records that are not completely running well and the efforts made by superiors provide briefings before carrying out duties and responsibilities, provide training in lifting techniques goods, make binding on goods and always monitored by the Bell Service Team and CCTV, further improve communication using HT (Handy Talky) or hotel phone, and check the luggage delivery log sheet.